FREE-SPACE, TWISTED LIGHT OPTICAL COMMUNICATION SYSTEM (2020)
Aspects of the subject disclosure may include, determining a twist number based on digital input data, wherein the twist number corresponds to a predetermined orbital angular momentum of a photon. Orbital angular momentum modulators adapted to change orbital angular momenta of an input signal are adjusted according to the twist number. Application of the input signal to the orbital angular momentum modulators applies orbital angular momenta to the input signal resulting in a twisted light signal having a predetermined number of twists based on the predetermined orbital angular momentum. Other embodiments are disclosed.